DECOLONIZING GLOBAL INTELLIGENCE towards inclusive interstellar statecraft. - NUNG WONG, PAK (ROUTLEDGE, 2026)
From September 11 to the calamitous withdrawal of United States troops from Afghanistan, Western intelligence has failed to negotiate the largest military and humanitarian crises across the world. This book proposes to decolonize global intelligence from the peripheries of the Global South and put forward a new intelligence practice of 'inclusive statecraft'.It shows how dominant Western intelligence systems have failed to protect the very ideas they promised to uphold and the discrepancy between the West's 'Responsibility to Protect (R2P)' liberalist doctrine and the realist on-the-ground complex reality as observed by the 'Failure to Protect (F2P)' scholarships. Drawing theoretical insights and empirical (both historical and contemporary) materials from a wide array of case studies of Western and non-Western intelligence settings and practices as well as their interactions, it argues that the next generation of global security and intelligence practitioners will necessitate genuine interracial, non-anthropocentric and cross-cultural inclusivity, especially the capability to take the non-Western intelligence cultures and their realist strategic thoughts seriously.This book will not just add new knowledge to the larger field of security and intelligence studies, but will also pioneer the relatively underdeveloped fields of comparative intelligence cultures, and interstellar intelligence/cultural studies. It will be indispensable for policymakers, bureaucrats and government officials.
Keywords: Security, International.; National security -- 21st century.; International relations -- History.; elektronické knihy; electronic books